CONSERVATION, SUSTAINABLE USE, TRADE AND INDUSTRY - Cunningham, A. B. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
This paper places the African traditional medicines trade into context through a comparison with Asia, suggesting that learning from Asia comes at an opportune time. The recent inter-Ministerial meeting in Libreville, Gabon (August 2008) on environment and health and the draft South African policy on African Traditional Medicine support this view. In Asia, particularly China, India, Pakistan and Vietnam, government support for the development and modernization of traditional medical systems is likely to increase harvest levels from wild stocks. Sustainable harvest of wild stocks is crucial as they continue to provide the main supply sources for 75-95% of species in trade in Asia and Africa.The resource base of the herbal medicines trade is being affected, however, by multiple factors simultaneously, at different spatial and time scales. The most serious of these are habitat loss and fragmentation, global climate change, species-specific over-exploitation and invasive species. Commercial trade, often driven by rapid urbanization combined with cultural values placed on traditional medicines, is a challenge facing conservation of medicinal plants in many parts of Asia, Africa and in some Latin American countries. In addition, some native medicinal plants are considered powerful and effective in treating common and chronic diseases and have been widely commoditized in China and India. Many of the same high-altitude genera or species harvested from the Himalayas for trade to large cities affect wild stocks in neighbouring countries. A massive traditional medicines trade also occurs in West Africa and in South Africa, similarly affecting favoured plant species in neighbouring countries.